Alcohol binge drinking in adolescence and psychological profile: Can the preclinical model crack the chicken-or-egg question? - Castelli, Valentina; Plescia, Fulvio; Maniaci, Giuseppe; Lavanco, Gianluca; Pizzolanti, Giuseppe; Brancato, Anna; Cannizzaro, Carla (Frontiers in Psychiatry, 2022)
During adolescence, internal and external factors contribute to engaging with alcohol binge drinking (ABD), putting at risk the neurodevelopment of brain regions crucial for emotional control and stress coping. This research assessed the prevalence of ABD in late adolescent students of Southern Italy and characterized their psychological profile and drinking motives. Translational effects of alcohol binge drinking in the animal model were also studied. Seven hundred and fifty-nine high school students of both sexes (aged 18–20) were recruited. Alcohol Use Disorder Identification Test-Consumption (AUDIT-C), Drinking Motives Questionnaire-Revised Short Form, Millon Clinical Multiaxial Inventory-Third Ed., State-Trait Anxiety Inventory, Connor-Davidson Resilience Scale, and Basic Self-Esteem Scale identified alcohol habits, drinking motives, and psychopathological profile. Eighty-five percentage of the students drank alcohol and 28% of them engaged in ABD; AUDIT-C correlated with enhancement, coping, and conformity motives. ABD was related to a greater likelihood of presenting clinical syndromes and personality disorders, as well as low resilience and self-esteem. Thereafter, in the pre-clinical model, adolescent male rats were exposed to alcohol (3.5 g/kg) in an intermittent binge-like paradigm and tested during prolonged abstinence. Rats were evaluated for anxiety-like behavior, motivated behaviors, resilience, and stress response following a psychosocial challenge. Binge-like alcohol-exposed adolescent rats displayed high integrated z-score for social- and novelty-induced anxiety, altered motivation-driven output, decreased resilience, and a blunted HPA axis response to psychosocial stress, with respect to respective controls. Our data confirm that ABD is the chosen pattern of drinking in a significant percentage of high school students in Southern Italy, and highlights AUDIT-C score as a relevant parameter able to predict the occurrence of affective disturbances. The evidence from the preclinical model shows that ABD produces detrimental consequences in the adolescent rat brain, resulting in negative affect, emotional dysregulation, and aberrant stress response, pointing to decreasing excessive alcohol drinking as a primary goal for the global act for brain health.